(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
A preschool educational institution is a unique world where the interests of children, parents, educators and staff collide. We should do all the work together to make the child feel comfortable, safe and happy in each preschool educational institution, so that the child attends there with joy. The participation rate in pre-school one year before formal entry into primary school is an impressive 72%, with low regional and gender disparities. This is an indication of the state’s strong commitment to providing compulsory free pre-school education, reinforced by the recently passed Pre-School Education and Training Act (2019).